PENINGKATAN HASIL BELAJAR DENGAN MODEL PROBLEM BASED LEARNING KELAS IV SD - Aini, Lidra; Reinita, Reinita; Miaz, Yalvema (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
The purpose of this research was to describe the improvement of integrated thematic learning outcomes using the Problem Based Learning (PBL) model at 4th grade of elementry school in Batu Taba. The research subjects were teachers and 27 students. Research site in Batu Taba. The result showed an increase in : a)RPP cycle I 80,55% (good) and cycle II 97,22% (very good) b)implementation in the aspects of teacher cycle I 78,12% (enough) and cycle II 93,75% (very good) c) implementation in the aspects of student cycle I 78,12% (enough) and cycle II 93,75% (very good) d) aseesment of the result of student alignment with the average in cycle I 70 and cycle II with an average of 95. Based on these results it can be concluded that the problem based learning (PBL) model can improve integrated thematic learning outcomes in students.Keyword : problem based learning, learning outcomes